Neuroprotective Effect of Red Betel (Piper crocatum) Extract on Brain Monosodium Gluatame (MSG)-Induced Rat (Rattus norvegicus) - Baihaki, Ichwan; Mutmainnah (Universitas Mohammad Husni Thamrin, 2024)
Indonesian people prefer to eat fast food which is generally rich in flavorings. The most common ingredient found in fast food is MSG (monosodium glutamate). MSG consumption that exceeds the limit will produce free glutamate which is excitotoxic in various organs, one of which is the neurological system. Red betel has a fairly high antioxidant content which can inhibit excitotoxicity by inhibiting the occurrence of free radicals. The aim of this research was to determine the neuroprotective effect of red betel extract (Piper crocatum) on the brains of rats (Rattus norvegicus) given monosodium glutamate (MSG). This research is a laboratory experimental study with a completely randomized design method using 5 treatment levels, namely negative control (NC), positive control (PC), treatment 1 (T1), treatment 2 (T2), treatment 3 (T3). The NC treatment level was given 2 mL of distilled water. The PC treatment level was given 7gr/KgBB MSG. Levels T1, T2, T3 were each given MSG 7gr/KgBW in the morning, then after 8 hours, level P1 was given 200mg/KgBW of red betel extract, P2 was given 400mg/KgBW of red betel extract, and P3 was given 600mg/KgBW of red betel extract. Examination of the number of neurons in the dentate gyrus of the hippocampus using the ImageJ application and examination of calcium ion levels using the RAPIDLab 348X tool. Data analysis used the One Way Anova test with the SPSS 24 program. The results showed that there was a significant difference (p<0.05) between PC and NC. The results of the calcium ion parameters showed that only the 600mg dose treatment group functioned as a protector in the occurrence of hypocalcemia, while the histopathology parameters showed that the 400mg and 600mg dose treatment groups functioned significantly as a neuroprotector.